STUDI GEOLOGI PENDAHULUAN EKSPLORASI BIJIH BESI DI KECAMATAN PELAIHARI KABUPATEN TANAH LAUT PROPINSI KALIMANTAN SELATAN - Prasetyanto, Inti Widi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
The aim of this preliminary geological study is to know the field conditions from iron ore, in the Gunung Tembaga, surrounding in Pelaihari District, Tanah Laut Regency, South Kalimantan Province, consist of geomorphological, stratigraphy and structural geo-logical aspect. Meanwhile the goals of the study is to know iron ore spreading in surface and its possibility occurrence in sub surface. The exploration methods has been done were preliminary geological survey and mapping consists of reference study, geological surface mapping, rock sampling and laboratory analysis. The Geomorphologically study area consists of undulating hilly with elevation from 30 until 80 meters. This morphology formed metamorphic rocks consists of schistfilit and igneous rocks consists of gabbro-peridotite. Those rocks overlay by colluvial deposits which found mafic igneous rocks fragment and iron ore scattered from sand, pebble until cobble. Structural geology in study area are joint and drag fold. Iron ore mineral in study area are magnetite, hematite and limonite which predicted from magmatic, replacement, residual or oxidation processes. Iron ore samples from study area show Fe value 66,14% and 66,20%.